Mitral valve prolapse, mitral annular disjunction, left ventricular basal hypertrophy and ventricular repolarization abnormalities in Marfan patients. (14th October 2021) - Delhomme, C; Lasne, A; Milleron, O; Arnoult, F; Delorme, G; Eliahou, L; Jadoui, S; Ould Ouali, N; Extramiana, F; Jondeau, G
Abstract: Background: Mitral annular disjunction (MAD) is a structural abnormality associated to mitral valve prolapse (MVP). MVP has been associated with malignant ventricular arrhythmia, originating from inferolateral left ventricle (LV) wall. However, the mechanism of these arrhythmias remains partly unknown and QT prolongation is probably a risk factor. Purpose: To take advantage of the high prevalence of MVP in Marfan syndrome (MFS) to study the relationship of MVP, MAD, LV basal hypertrophy and QTc. Methods: We conducted a prospective, monocentric and observational study. We included all MFS patients older than 14 yo without a history of thoracic surgery seen in the French reference center between 01/01/2015 and 01/01/2017. A standardized transthoracic echocardiography was systematically performed and recorded. We identified presence of MAD and measured its length, measured end-systole and end-diastole mitral annular diameters. MVP was identified on echocardiography as systolic displacement (≥2mm) of a mitral leaflet into the left atrium, beyond the mitral annular plane. Mitral valve billowing was identified as systolic displacement of a mitral leaflet in the mitral annular plane or less than 2 mm into the left atrium. We evaluated LV inferolateral wall thickness: basal inferolateral hypertrophy (BILH) was defined as basal inferolateral thickness ≥12mm and basal to mild wall thickness ratio ≥1.5. A rest 12-lead ECG was performed and used to measure QTc according to Bazet rules. Results: 250 MFS patients (median age 30.8 years) were included. Systolic mitral leaflet displacement abnormality (billowing or MVP) was present in 187 (74.8%) patients and MVP in 93 (37.2%). MAD was present in 52/235 (22.13%) and was associated with billowing or MVP in all cases. End-systole mitral annular diameter was larger when billowing or MVP was present (mean: 34.82mm vs. 30.53mm, p<0.0001) and in MAD+ than in MAD− (mean: 37.14mm vs. 32.46mm, p<0.0001) with a correlation between MAD length and end-systole mitral annular diameter (r=0.395, p<0.0001). Whereas mitral annular diameter decreased in systole in MAD−, it increased in MAD+ (mean mitral annular diameter (diastolic–systolic): 3.69mm vs. −0.87mm, p<0.0001). Basal inferolateral wall was thicker in MAD+ than MAD− (mean: 11.39mm vs. 10.11mm, p=0.016). BILH was present in 18/175 (10.29%) patients with billowing or MVP vs. in 1/59 (1.69%) without (p=0.0367) and in 9/50 (18%) MAD+ vs. 10/174 (5.75%) MAD− (p=0.006). No electric abnormality on ECGs was associated with MAD+, billowing or MVP. In contrast, patients with BILH had a longer QTc than patients without hypertrophy (mean: 426ms vs. 411.4ms, p=0.0220). Conclusion: In our MFS population, MAD is associated with systolic mitral annular dilatation, MVP or billowing and basal LV hypertrophy, but not with ECG abnormalities. Only patients with basal hypertrophy present a QTc prolongation, a known risk marker for ventricular arrhythmias. Funding Acknowledgement: Type of funding sources: None.